Temperature Dependent X-ray Powder Diffraction Study of Pb2,5Sb1,5O6,75 - Ismunandar Ismunandar; Yoni Budiman (Indonesian Journal of Physics, 2002)
It has been reported that Pb2,5Sb1,5O6,75 adopts an ideal pyrochlore structure at room temperature and transforms to a weberite structure at high temperature. In order to study the structure transformation, structures of Pb2,5Sb1,5O6,75 as afunction of temperature (25°C < T < 950 °C) have been studied using in-situ diffraction techniques. The structures were determined from X-ray powder diffraction data using the Rietveld analysis. No structural phase transitions were observed in the range 25°C to 750°C, so the structure of Pb2,5Sb1,5O6,75 was concluded to be an ideal pyrochlore structure. The cubic lattice parameter increases linearly from a = 10,6924(5) Å to 10,7521(10) Å. Diffraction patterns above 850°C can be indexed in a related orthorhombic structure indicating n possible weberite structure. Thermal analysis using DTA & TGA of Pb2,5Sb1,5O6,75 showed that the change at 850oC were accompanied by a weight loss. From the weight loss, it can be concluded that the orthorhombic phase has the composition of Pb2Sb2O6.